Answer:
[tex]log_n(m)= \frac{4}{3}[/tex]
Step-by-step explanation:
N^4/3=m
[tex]n^{4/3}=m[/tex]
We need to write the equation in logarithmic form
we take log on both sides
[tex]log(n^{4/3})=log(m)[/tex]
We apply log property to remove the exponent 4/3
As per log property we can move exponent before log
log(a^m) = m log (a)
So our equation becomes
[tex]\frac{4}{3}log(n)=log(m)[/tex]
Now we divide both sides by log(n)
[tex]\frac{4}{3} =\frac{log(m)}{log(n)}[/tex]
Now we apply change of base formula
log(a)/ log(b)= log_b(a)
[tex]\frac{4}{3} =log_n(m)[/tex]
So log form is
[tex]log_n(m)= \frac{4}{3}[/tex]